Near unity ideality factor for sidewall Schottky contacts on un-intentionally doped β-Ga2O3. (13th March 2019) - Zhang, Yuewei; Mauze, Akhil; Alema, Fikadu; Osinsky, Andrei; Speck, James S.
Abstract: We report a plasma damage removal method for β -Ga2 O3 devices using hot phosphoric acid solution. Sidewall Schottky diodes were fabricated on MOCVD-grown un-intentionally doped β -Ga2 O3 films grown on (010)-oriented semi-insulating substrates. Removal of the plasma damaged layers using wet etching resulted in near unity ideality factor and reduced hysteresis. The anisotropic etching behavior on the electrical characteristics of the devices was further evaluated, and the [001] direction was found to be a favorable direction for vertical device fabrications. The demonstrated damage removal method could enable a range of novel device architectures, including high power vertical diodes, vertical transistors and ultra-scaled devices.